2022
DOI: 10.18502/ijpa.v17i1.9010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Laboratory Characteristic, and Treatment of Human Toxocariasis in Northern Vietnam

Abstract: Background: We determined the occurrence frequency of Clinical signs, subclinical characteristics on positive anti-IgG Toxocara ELISA cases, and clinical response results after 1 month of albendazole-specific treatment.  Methods: A number of 103 clinically treated patients were studied between 2018 and 2019 in two hospitals. Relevant data are collected from examination and medical records such as age, sex, job, resident, clinical and sub-clinical signs. Sera samples were subjected to anti-IgG Toxocara an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Because the diagnosis of this parasitic infection in humans is subject to serological examination that detects antibodies against Toxocara excretory-secretory (TES) antigens. This test, however, has low specificity (cross-reactions with other helminths) and is not capable of discriminating the asymptomatic form from those that lead to other syndromes, or historical chronic or acute infections [24,25].…”
Section: Toxocara and Its Perpetuity In Urban Communitiesmentioning
confidence: 99%
“…Because the diagnosis of this parasitic infection in humans is subject to serological examination that detects antibodies against Toxocara excretory-secretory (TES) antigens. This test, however, has low specificity (cross-reactions with other helminths) and is not capable of discriminating the asymptomatic form from those that lead to other syndromes, or historical chronic or acute infections [24,25].…”
Section: Toxocara and Its Perpetuity In Urban Communitiesmentioning
confidence: 99%
“…In most human toxocariasis cases, serious symptoms do not appear, although in some cases symptoms such as eye inflammation, retina damage, blurred vision, skin rashes, breathing difficulties, abdominal pain, fever, coughing, loss of appetite and fatigue had been reported (Thu et al, 2022). Studies also revealed that toxocariasis is more prevalent in children (Foroutan et al, 2022;Heidari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…After ingestion, parasitic larvae penetrate the intestinal wall and move to a variety of organs, including the brain, eyes, lungs, and liver, through blood circulation and may cause clinical manifestations, such as visceral and ocular larva migrans, covert Toxocara infection, eosinophilic meningoencephalitis and neurotoxocariasis. In most human toxocariasis cases, serious symptoms do not appear, although in some cases symptoms such as eye inflammation, retina damage, blurred vision, skin rashes, breathing difficulties, abdominal pain, fever, coughing, loss of appetite and fatigue had been reported (Thu et al, 2022). Studies also revealed that toxocariasis is more prevalent in children (Foroutan et al, 2022; Heidari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%